1994
DOI: 10.1016/0035-9203(94)90237-2
|View full text |Cite
|
Sign up to set email alerts
|

Aminosidine (paromomycin) versus sodium stibogluconate for the treatment of American cutaneous leishmaniasis

Abstract: The efficacy of aminosidine was compared with sodium stibogluconate in an open, randomized study of parasitologically-proven cutaneous leishmaniasis in Belize. Aminosidine, 14 mg/kg/d (max. 1 g daily) for 20 d, healed 10 of 17 lesions and sodium stibogluconate, 20 mg/kg/d for 20 d, healed 15 of 17 lesions. Lesions caused by Leishmania braziliensis were relatively unresponsive to aminosidine. Aminosidine was well tolerated and toxicity was not observed. Sodium stibogluconate was not well tolerated and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…Published efficacy trials of pentavalent antimonial drugs using a regimen of 20 mg Sb/kg/d for 20 days in Colombia and the Americas, have documented an efficacy of 88 to 100% for the treatment of cutaneous leishmaniasis caused by species of the Leishmania Viannia subgenus. 5,8,[13][14][15][16]20 One group in the Colombian southwest and close to our study area, reported efficacy of meglumine antimonate with a 15-day regimen, to be 40%, 21,22 and close to the 36-37% efficacy of placebo reported by other investigators in other areas of Colombia. 8,20 All of these trials have involved young-adult populations primarily.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Published efficacy trials of pentavalent antimonial drugs using a regimen of 20 mg Sb/kg/d for 20 days in Colombia and the Americas, have documented an efficacy of 88 to 100% for the treatment of cutaneous leishmaniasis caused by species of the Leishmania Viannia subgenus. 5,8,[13][14][15][16]20 One group in the Colombian southwest and close to our study area, reported efficacy of meglumine antimonate with a 15-day regimen, to be 40%, 21,22 and close to the 36-37% efficacy of placebo reported by other investigators in other areas of Colombia. 8,20 All of these trials have involved young-adult populations primarily.…”
Section: Discussionsupporting
confidence: 83%
“…The overall low efficacy of pentavalent antimonials in this population and the relationship of age with poor clinical response would not have been detected in the adult male populations usually recruited for efficacy studies. 5,8,13,15,16 This study was designed as a two-arm active-medicine clinical trial because the use of placebo was considered unethical in view of the risk of mucosal or cutaneous relapses reported previously in the area. 17 The results did not reveal significant differences in efficacy between 10 and 20 days of supervised treatment with 20 mg Sb/kg/d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding coincide with that obtained by Hepburn et al (1994) where it was possible that Leishmania present in clinically treated lesion, hence a post treatment culture is useful. This finding has an applicable medical importance, that patient treated with one of antileishmanial drug and showed marked clinical response, should be carefully examined for fear of the presence of viable parasite which may have important consequence if the patient subsequently becomes immunosuppressed.…”
Section: Discussionsupporting
confidence: 77%
“…The use of injectable paromomycin is not effective against CL. 19,20 However, its topical use as an ointment cured CL caused by species of the New and Old World, especially when supplemented with gentamicin. [21][22][23][24][25] However, the efficacy may vary.…”
Section: Introductionmentioning
confidence: 99%